Pneumatic balloon dilatation versus laparoscopic Heller's myotomy in idiopathic achalasia - Hlatshwayo, Sabelo Jabulani (Department of Public Health and Family Medicine, 2016)
Background Both laparoscopic Heller's myotomy (LHM) and pneumatic balloon dilatation (PBD) are widely used in the management of achalasia, but there is still no clarity as to which of these interventions is the best treatment for patients with the condition. Methods Newly diagnosed achalasia patients were randomised into PBD or LHM. The severity of achalasia symptoms in all participants was documented using the Eckardt score, a clinical symptom score whose components are dysphagia, chest pain, regurgitation and weight loss. The Eckardt score ranges from 0 in those with no symptoms to 12 in patients with pronounced symptoms. The primary outcome, therapeutic success, was defined as a drop in the Eckardt score to <3 or subsequent need for alternative intervention. The secondary outcome was the complication rate, including mortality, in the two treatment arms.